2019
DOI: 10.1111/adb.12744
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant insular cortex connectivity in abstinent alcohol‐dependent rats is reversed by dopamine D3 receptor blockade

Abstract: A few studies have reported aberrant functional connectivity in alcoholic patients, but the specific neural circuits involved remain unknown. Moreover, it is unclear whether these alterations can be reversed upon treatment. Here, we used functional MRI to study resting state connectivity in rats following chronic intermittent exposure to ethanol. Further, we evaluated the effects of SB-277011-a, a selective dopamine D3 receptor antagonist, known to decrease ethanol consumption. Alcohol-dependent and control ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…including the infralimbic and prelimbic areas seems therefore genuine in msP rats, and a property that this line shares with the post-dependent model, in which rodents are exposed to high blood alcohol levels during chronic intermittent ethanol (Meinhardt and Sommer, 2015). Prolonged alcohol exposure caused a profound reprogramming in the mPFC, leading to molecular dysregulation (Heilig et al, 2017) and alterations in activity and connectivity (Scuppa et al, 2020) 14 that probably contribute to the alcohol-dependent phenotype. Similar alterations appear to preexist in the msP line (Bjork et al, 2010;Bifone et al, 2019).…”
Section: Discussionmentioning
confidence: 81%
“…including the infralimbic and prelimbic areas seems therefore genuine in msP rats, and a property that this line shares with the post-dependent model, in which rodents are exposed to high blood alcohol levels during chronic intermittent ethanol (Meinhardt and Sommer, 2015). Prolonged alcohol exposure caused a profound reprogramming in the mPFC, leading to molecular dysregulation (Heilig et al, 2017) and alterations in activity and connectivity (Scuppa et al, 2020) 14 that probably contribute to the alcohol-dependent phenotype. Similar alterations appear to preexist in the msP line (Bjork et al, 2010;Bifone et al, 2019).…”
Section: Discussionmentioning
confidence: 81%
“…With regard to increased functional connectivity between the insula and CPu, S1BF, and PnO regions, research has shown that functional connections decreased between the insula and CPu in alcohol-dependent rats going through early withdrawal [ 46 ]. Both the insula and S1BF have also been shown to belong to the circuit which regulate gustatory information [ 47 ], and connections between the insula and PnO are yet to be explored, with more research required in these areas overall.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings to alcohol use disorder are also evident in animal models. With regard to abstinence, aberrant or reduced, connectivity of the insular cortex is observed in post-dependent rats compared to naïve controls (Scuppa et al, 2020). Additionally, the insular cortex of conscious rats is activated following acute (six days) Pavlovian conditioning of alcohol-associated cues in an awake fMRI paradigm (Tsurugizawa et al, 2012).…”
Section: The Role Of the Anterior Insular Cortex In Animal Models Of Alcohol Use Disordermentioning
confidence: 99%
“…As stated above, there is a strong projection between the insular cortex and the striatum. Indeed, recent imaging studies have shown alcoholdependent rats have altered insular cortex activity and connectivity which can be partially restored by systemic dopamine D 3 receptor antagonism (Scuppa et al, 2020). Alcohol also disrupts µ-opioid receptor-mediated long-term synaptic depression at anterior insular cortex-dorsolateral striatum synapses (Munoz et al, 2018).…”
Section: The Role Of the Anterior Insular Cortex In Animal Models Of Alcohol Use Disordermentioning
confidence: 99%